2019
DOI: 10.1109/access.2019.2955307
|View full text |Cite
|
Sign up to set email alerts
|

Image-Based Learning to Measure the Stopped Delay in an Approach of a Signalized Intersection

Abstract: Traffic delays are inevitable when evaluating the performance of a signalized intersection, but these delays cannot be directly measured in the field based on existing spot detectors. Traffic-light controllers have adopted a reinforcement learning (RL) algorithm, which is currently prevalent in the field of study and requires real-time measurement of traffic delays to derive the state and reward for each time period. No RL-based study, however, has provided a robust way to measure traffic delays. In order to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
6
0
7
Order By: Relevance
“…However, there may be skepticism regarding how to accurately measure these parameters when an RL algorithm is implemented in the field. Our two previous studies showed strong evidence that they can be measured onsite based solely on video images (Shin et al, 2019;Chung and Sohn, 2017). The state was defined for each lane group that is comprised of one or more lanes that share a common stop-line and capacity.…”
Section: The Definition Of Statementioning
confidence: 99%
“…However, there may be skepticism regarding how to accurately measure these parameters when an RL algorithm is implemented in the field. Our two previous studies showed strong evidence that they can be measured onsite based solely on video images (Shin et al, 2019;Chung and Sohn, 2017). The state was defined for each lane group that is comprised of one or more lanes that share a common stop-line and capacity.…”
Section: The Definition Of Statementioning
confidence: 99%
“…Researchers have also relied on dynamic approaches for delay estimation using state space modelling and filtering techniques [11][12][13][14]. Researchers have also used more dataintensive techniques like time series analysis, k-means clustering, and other artificial intelligence based solutions for delay estimation [15][16][17][18][19][20]. Researchers have also employed various metaheuristic approaches like genetic algorithm, differential evolution, harmony search, and artificial bee colony for estimating and optimising intersection delay [21][22][23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, YOLO requires additional training whenever the testbed changes. Drawing a bounding box for every vehicle in training images entails considerable human effort, but it is required in order to accurately recognize vehicles in photos taken from different viewpoints [22].…”
Section: Introductionmentioning
confidence: 99%
“…To tackle the problem, original images were simplified using a CycleGAN developed by [23], so that both vehicles and backgrounds would have monotone colors. Such a transformation had already been successfully adopted in our previous studies measuring traffic speed and delay [22,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation